Satellite observations of land surface temperature patterns induced by synoptic circulation. (14th March 2014) - Lensky, Itamar M.; Dayan, Uri
ABSTRACT Land surface temperature (LST) controls physical, chemical and biological processes on earth, and is used for assessing climatic changes. The seasonal and diurnal cycles, cloud cover, surface properties and atmospheric processes at several scales govern the LST, leading to its high spatial and temporal variability. In this study, a first attempt to assess the contribution of the synoptic scale circulation on LST is carried over using 2000–2012 MODIS data over the East Mediterranean (EM). This is demonstrated for 6 out of 19 synoptic circulation patterns characterizing the EM in the winter, summer and spring. Mean LST data calculated for each synoptic category (LSTsyn_cat) showed mainly the seasonality, i.e. climatological signal (LSTclim). In order to remove the seasonality, we used the LST anomaly (LSTsyn_cat − LSTclim), which 'cleaned' also the effects of vegetation and mineralogy, revealing the effects of circulation. Surface air temperature anomalies (at 995 sigma level) retrieved from NCEP/NCAR reanalysis calculated for the same synoptic categories were consistent with those of LST. This confirms the ability of remote sensing to detect the effect of the synoptic scale circulation on the spatial distribution of LST.